The Effect of Service Quality, Trust Members on Member Loyalty through Member Satisfaction - Septi Novianingsih, Veronika; Kardoyo, Kardoyo; Thomas, Partono (Universitas Negeri Semarang, 2019)
This study aims to analyze and describe the effect of service quality, member trust on member loyalty through member satisfaction. The research approach used a quantitative method with path analysis which was processed using SPSS. The subjects of the research were all members of the KSP CU Pangudi Luhur Kasih. The research samples were 96 respondents, with cluster sampling techniques. The results showed (1) there was not a positive relationship between service quality variables on member loyalty, (2) there was a positive relationship between member trust variables on member loyalty, (3) there was a positive relationship between member satisfaction variables on member loyalty, (4) there was not a positive relationship between service quality variables on member satisfaction, (5) there was a positive relationship between member trust variables on member satisfaction, (6) there was not a relationship between service quality variables on member loyalty through member satisfaction, (7) there was a positive relationship between variables member trust on member loyalty through member satisfaction.